STA/LTA trigger algorithm implementation on a seismological dataset using Hadoop MapReduce - Youness Choubik; Abdelhak Mahmoudi; Mohammed Majid Himmi; Lahcen El Moudnib (Institute of Advanced Engineering and Science, 2020)
In this work we implemented STA/LTA trigger algorithm, which is widely used in seismic detection, using Hadoop MapReduce. Thisimplementation allows to ﬁnd out how effective it is in this type of tasks as well as to accelerate the detection process by reducing the processing time. We tested our implementation on a seismological dataset of 14 broadband seismic stations and compare it with the traditional one. The results show that MapReduce decreased the processing time by 34% compared to the traditional implementation.